Contested social orders: negotiating urban security in Nigeria and South Africa - (:unkn) unknown (My University, 2013)
[...] The aim of this chapter is threefold. Firstly, we would like to unpack the empirical reality of state and non-state ordering using Nigerian and South African policing systems as our "theatres" [...] Secondly, we would like to reflect on the consequences of diverse or plural non-state ordering, such as the challenges that arise with respect to the inequitable delivery of security/policing [...] The third aim of this chapter is to question our current conceptual framing of state and non-state...
Keywords: African Research